The Level of Independence of the Elderly in the Activity of Daily Living (ADL) at Tresna Werdha Nirwarna Puri Samarinda Social Home Using the Barthel Index Method - Muhammad Aminuddin; M Kapriliansyah; Dwi Nopriyanto (Fakultas Kedokteran, 2020)
Background: The elderly are part of the process of growth and development. Humans do not suddenly grow old but develop from babies, children, adults and eventually grow old. Physical changes and predictable behavior that occurs in all people when they reach the age of certain stages of chronological development. Increasing the number of older people will cause various problems such as health problems, physical problems and other problems. Objective: to find out the description of the level of independence of the elderly in Activity Of Daily Living (ADL) at PSTW Nirwarna Puri Samarinda by using the Barthel Index Method. Method: Quantitative descriptive research with survey approach using questionnaire sheets. Results: The description of the level of independence of the elderly in the Activity of Daily living shows that the majority of the elderly as many as 19 elderly (63.33%) belong to the independent category, nine elderly (30%) fall into the category of moderate dependence, one elderly (3.33% ) included in the category of heavy dependency and one elderly (3.33%) included in the category of mild dependence. That most of the PSTW Nirwarna Puri Samarinda have an independent category in carrying out daily activities. Conclusion: The level of independence of the elderly at PSTW Nirwarna Puri Samarinda mostly shows an independent category. Suggestion: The positive activities of gymnastics and other activities that are supported expected to maintain the health of the elderly which has an impact on the independence of the elderly.Keywords: Level Independence, Activity Daily Living, Barthel Index